MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMECAHAN MASALAH MATEMATIKA: PERSPEKTIF FILSAFAT DAN ADVERSITY QUOTIENT - Siswanto, Eko; Aziz, Tian Abdul; El Hakim, Lukman (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to explain critical thinking skills in solving mathematics problems using a philosophical perspective, especially from Progressive Education Theory and Adversity Quotient. The research method used is a literature study by utilising primary data in the form of books, online journals, and seminars that discuss critical thinking skills, problem solving, John Dewey's Progressive Education Theory, and Adversity Quotient. The results of data analysis show that critical thinking skills have a central role in dealing with mathematical problems. John Dewey's Progressive Education Theory can be a guide for teachers in choosing learning models that encourage students' active involvement in the learning process in the classroom. Meanwhile, Adversity Quotient has a positive influence on critical thinking ability.